Pressure Control Strategy of Coiled Tubing Blowout Preventer Control System - Hu Yaxuan; Wu Wenxiu (Shiyou jixie, 2025)
The wall of coiled tubing is relatively thin and its pressure-bearing capacity is limited. To avoid damage to coiled tubing or inability to quickly nip off coiled tubing during the operation of the blowout preventer， a control strategy for outlet pressure of blowout preventer control system was studied. To solve the problem of slow response and poor control accuracy in conventional PID control， fuzzy theory was combined with PID control technology to form fuzzy PID control， so as to improve the pressure control accuracy and response speed of the control system. By means of building a mathematical model of electromagnetic relief valve - the main actuator in the control system， the MATLAB/Simulink simulations were used to obtain the step responses of fuzzy PID control and conventional PID control respectively， and the results were compared and analyzed. The study results show that the response speed of fuzzy PID control is 21.44% faster， the accuracy is improved by 1.33% and the overshoot is reduced by 13% compared to conventional PID control， resulting in a significant improvement in control quality. The study conclusions provide a new solution to pressure control of coiled tubing control system， making the action of the blowout preventer more reliable and faster.